2020
DOI: 10.1039/d0cy01451f
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzed chain growth polymerisation of ethylene using lanthanidocenes/dialkylmagnesium: further developments and one pot synthesis of narrow dispersed high molecular weight fatty alcohols

Abstract: Ethylene polymerisation on dialkylmagnesium using neodymocene based catalysts via Catalyzed Chain Growth (CCG) has been studied with the aim to improve the performance of the overall catalytic/transfer process. A one...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…This in situ synthetic strategy showed the same efficiency as the standard approach including the synthesis and purification of neodymium biscyclopentadienylchloro complex. 96 Polyethylenes bearing cyclopentadienyl (Cp) end groups 97 were obtained through a transformation of previously incorporated iodide chain ends that were synthesized via CCG of ethene on magnesium with the following iodine termination/functionalization (Scheme 30a). 94 PE-I (M n = 1.4 kg•mol −1 ; Đ = 1.2) reacted with bis(cyclopentadienyl)nickel (NiCp 2 ) in the presence of Ph 3 P to generate Cp terminated polyethylenes (PE-Cp, Scheme 32) with 72% functionalization efficiency (Table 3).…”
Section: Cctp For End Functionalization Using Conventional Ctasmentioning
confidence: 99%
See 1 more Smart Citation
“…This in situ synthetic strategy showed the same efficiency as the standard approach including the synthesis and purification of neodymium biscyclopentadienylchloro complex. 96 Polyethylenes bearing cyclopentadienyl (Cp) end groups 97 were obtained through a transformation of previously incorporated iodide chain ends that were synthesized via CCG of ethene on magnesium with the following iodine termination/functionalization (Scheme 30a). 94 PE-I (M n = 1.4 kg•mol −1 ; Đ = 1.2) reacted with bis(cyclopentadienyl)nickel (NiCp 2 ) in the presence of Ph 3 P to generate Cp terminated polyethylenes (PE-Cp, Scheme 32) with 72% functionalization efficiency (Table 3).…”
Section: Cctp For End Functionalization Using Conventional Ctasmentioning
confidence: 99%
“…95 High molecular weight fatty alcohols (C30-C40) were synthesized with 90% functionalization efficiency (Table 3) and with narrow molar mass distribution (Đ ≈ 1.1), applying (C 5 Me 5 ) 2 NdCl 2 Li(OEt 2 ) 2 (29, Figure 9)/n-BuEtMg catalyzed CCG polymerization of ethene followed by oxidation with diluted O 2 (20% in Ar). 96 It was also revealed that the addition of appropriate ether (e.g., tetraglyme or dimethoxyethane) increases the catalytic activity due to the dissociation of magnesium dialkyls or Cp R 2 Nd-(μ-R) 2 -MgR moieties (Scheme 31). Moreover, the authors proposed a one pot in situ alkylation method based on simple neodymium salt (Nd-(BH 4 ) 3 (THF) 3 ) and various substituted cyclopentadienes (Cp R H) for the catalyst synthesis (Scheme 31), which does not require the isolation of the neodymium biscyclopentadienylchloro complex.…”
Section: Cctp For End Functionalization Usingmentioning
confidence: 99%
“…In these CCG reactions, Mg(PE) 2 is used to generate various end-functionalised PE-X. 43,44,[47][48][49][50] Here we report our studies on the iron-based CCG reaction using ZnEt 2 to prepare Zn(PE) 2 with defined chain lengths and conversion to a range of end-functionalised PE-X materials. While the reactivity of Zn(PE) 2 in many ways resembles that of Mg(PE) 2 , key advantages of the Fe/Zn system are the ease of synthesis and handling of the iron-based catalyst, the use of highly abundant and cheap first row metals iron and zinc, and crucially, the absence of any alkene by-products, which is often seen in other systems.…”
Section: ð1þmentioning
confidence: 99%
“…End-functionalised PE-X can then be used for the preparation of diblock copolymers. 8,22,[36][37][38][39][40][41] Oxidative workup of the M-C bonds to generate PE-OH has been reported for aluminium, 21,23,42 magnesium, 43,44 and zinc alkyls. [36][37][38][39][40][41]45,46 The end-functionalisation of polyethylene using magnesium alkyls as the chain transfer agent in combination with a neodymium polymerisation catalyst [(C 5 Me 5 ) 2 NdCl 2 Li(OEt 2 ) 2 ], first reported by Mortreux, 24 has been extensively investigated by Boisson and D'Agosto and co-workers.…”
Section: ð1þmentioning
confidence: 99%
See 1 more Smart Citation